History, field definition and management studies: the case of the New Deal. Issue 2 (8th April 2014) - Foster, Jason; J. Mills, Albert; Weatherbee, Terrance
Abstract : Purpose: – The aim of this paper is threefold. First, to argue for a more historically engaged understanding of the development of management and organization studies (MOS). Second, to reveal the paradoxical character of the recent "historical turn, " through exploration of how it both questions and reinforces extant notions of the field. Third, to explore the neglect of the New Deal in MOS to illustrate not only the problem of historical engagement, but also to encourage a rethink of the paradigmatic limitations of the field and its history. Design/methodology/approach: – Adopting the theory of ANTi-history, the paper conducts an analysis of historical management textbooks and formative management journals to explore how and why the New Deal has been neglected in management theory. Findings: – Focussing on the New Deal raises a number of questions about the relationship between history and MOS, in particular, the definition of the field itself. Questions include the ontological character of history, context and relationalism, and the link between history and MOS, ethics, Anglo-American centredness, and the case for historical engagement. Originality/value: – The paper argues for a new approach to historical understanding that encourages a revisiting of what constitutes the field of MOS; a greater awareness of and opening up to alternative (hi)stories and, thus, approaches to MOS; and a re-evaluation of phenomena such as the New Deal and other more radical ways of organizing.